First evidence of a large predatory plesiosaurian from the Lower Cretaceous non-marine 'Wealden facies' deposits of northwestern Germany. Issue 4 (2nd October 2018) - Sachs*, Sven; Hornung, Jahn J.; Lallensack, Jens N.; Kear, Benjamin P.
Abstract : Sachs, S., Hornung, J.J., Lallensack, J.N. & Kear, B.P., November.2017. First evidence of a large predatory plesiosaurian from the Lower Cretaceous non-marine 'Wealden facies' deposits of northwestern Germany. Alcheringa 42, 501-508. ISSN 0311-5518. Here, we describe the incomplete mandible of a large-skulled 'pliosauromorph' plesiosaurian from the Lower Cretaceous (Berriasian) of northwestern Germany. The fossil derives from limnic–brackish 'Wealden facies' deposits of the Deister Formation (Bückeberg Group), and is preserved as a natural mould in fine-grained sandstone. Examination of the original remains, in conjunction with a three-dimensional photogrammetrically digitized 'cast', revealed a conspicuous rosette of symphyseal alveoli, which would otherwise typically characterize Early–Middle Jurassic macrophagous plesiosaurians including rhomaleosaurids and the pliosaurid Simolestes . The Deister Formation 'pliosauromorph' represents the first record of a large-bodied plesiosaurian macrocarnivore from the 'Wealden-facies' strata of Europe, and thus adds a previously unrecognized trophic level of aquatic apex predators to the Early Cretaceous non-marine ecosystems of Europe. Sven Sachs* [ sachs.pal@gmail.com ] Naturkunde-Museum Bielefeld, Abteilung Geowissenschaften, Adenauerplatz 2, 33602 Bielefeld, Germany and Im Hof 9, 51766 Engelskirchen, Germany; Jahn J. Hornung [ jahn.hornung@yahoo.de ] Niedersächsisches Landesmuseum Hannover, Willy-Brandt-Allee 5, 30169 Hannover, Germany; Jens N. Lallensack [ jens.lallensack@uni-bonn.de ] Steinmann-Institut für Geologie, Mineralogie und Paläontologie, Rheinische Friedrich-Wilhelms-Universität Bonn, Nussallee 8, 53115 Bonn, Germany; Benjamin P. Kear [ benjamin.kear@em.uu.se ] Museum of Evolution, Uppsala University, Norbyvägen 16, Uppsala SE-752 36, Sweden.